Transcriptome analysis of Pacific white shrimp (Liptopenaeus vannamei) after exposure to recombinant Vibrio parahaemolyticus PirA and PirB proteins. Issue 132 (January 2023) - Lange, Miles D.; Abernathy, Jason; Rawles, Anna A.; Zhang, Dunhua; Shoemaker, Craig A.; Bader, Troy J.; Beck, Benjamin H.
Abstract: Vibrio parahaemolyticus is a Gram-negative bacterium commonly found in marine and estuarine environments and is endemic among the global shrimp aquaculture industry. V. parahaemolyticus proteins PirA and PirB have been determined to be major virulence factors that contribute significantly to the development of acute hepatopancreatic necrosis disease. Our previous work had demonstrated the lethality of recombinant PirA and PirB proteins to Pacific white shrimp ( Liptopenaeus vannamei ). To understand the host response to these proteins, recombinant PirA and PirB proteins were administered using a reverse gavage method and individual shrimp were then sampled over time. Shrimp hepatopancreas libraries were generated and RNA sequencing was performed on the control and recombinant PirA/B-treated samples. Differentially expressed genes were identified among the assayed time points. Differentially expressed genes that were co-expressed at the later time points (2-, 4- and 6-h) were also identified and gene associations were established to predict functional physiological networks. Our analysis reveals that the recombinant PirA and PirB proteins have likely initiated an early host response involving several cell survival signaling and innate immune processes. Highlights: RNA sequencing performed to evaluate the shrimp host response to Vibrio toxin. Differential gene expression identified in the shrimp hepatopancreas post-exposure to Vibrio toxin. The shrimp host response activated regulatory pathways, including cell survival signaling and innate immune processes.